2013
DOI: 10.1590/s1413-70542013000600004
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals availability and soil fertility after land application of sewage sludge on dystroferric Red Latosol

Abstract: Sewage sludge is the solid residue obtained from urban sewage treatment plants. It is possible to use the sludge in a sustainable way as fertilizer and as soil conditioner due to its high levels of organic matter and nutrients. Besides pathogens and volatile organic compounds, the residue may also contain heavy metals which may accumulate and contaminate crops and the food chain. The aim of this study was evaluates the changes in the fertility of dystrophic Red Latosol and in the availability of heavy metals f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…The ratio of Cd content increase is higher than those for Pb, Cu and Zn [41][42][43]. Wang and co-worker indicated that the addition of 40 t of sewage sludge per ha in rice production resulted in the build-up of about 4, 5, 2, and 11 times more of Cd, Cr, Ni and Pb, respectively, in comparison with non-treated soil.…”
Section: Sewage Sludge Characterizationmentioning
confidence: 99%
“…The ratio of Cd content increase is higher than those for Pb, Cu and Zn [41][42][43]. Wang and co-worker indicated that the addition of 40 t of sewage sludge per ha in rice production resulted in the build-up of about 4, 5, 2, and 11 times more of Cd, Cr, Ni and Pb, respectively, in comparison with non-treated soil.…”
Section: Sewage Sludge Characterizationmentioning
confidence: 99%
“…Although the increase of the SS rates promoted an increment of Zn in the soil (Table 5), the SS2 treatment presented higher Zn content in the leaves (Figure 2). This result can be explained by the increase in soil organic matter content, which can complex this element, reducing its availability to plants (Moreira;Mincato;Santos, 2013).…”
Section: Uptake and Translocation Of Nutrients And Potential Toxic Elmentioning
confidence: 99%
“…Another factor that limits the use of SS in agriculture is the risk of soil and food contamination by heavy metals (Abreu-Junior et al, 2019;Moreira;Mincato;Santos, 2013). Some metals are essential nutrients required in small contents by the plants.…”
Section: Introductionmentioning
confidence: 99%
“…Also, LOPEZ-LUNA et al (2012) have shown an accumulation of Cr in the shoot of common bean with the application of tannery sludge. In general, Cr uptake by the plants accumulates in the roots and forms barriers that diminish their translocation to the shoot (MOREIRA et al, 2013). The biological N fixation, being a process carried out at the root level, can be influenced by the excessive presence of Cr due to the alteration of the biochemical processes of the microorganisms and direct toxicity on Bradyrizobium (HUNGRIA & VARGAS, 2000) and rhizobia symbiosis (STAMBULSKA et al, 2018).…”
Section: Cts (Mg Hamentioning
confidence: 99%